A Persistent Foe: Reinvigorating the Fight against Cardiovascular Disease in a Changing World - Kumar, Arun HS (Biology, Engineering, Medicine and Science Reports)
For decades, Cardiovascular Disease (CVD) has cast a long shadow over humanity, claiming millions of lives each year. While advancements in medicine have yielded undeniable progress, a recent study published in The Lancet paints a disquieting picture.1 Life expectancy has undoubtedly improved globally,2 but a concerning stagnation in the decline of CVD mortality since 2009 demands our urgent attention. The study lays bare a fascinating paradox of our time. While it celebrates the undeniable progress in healthcare, it also unveils a hidden challenge. On the one hand, we witness a remarkable decline in mortality rates from previously dominant killers like stroke and lower respiratory infections.3,4 This translates into a demonstrably extended lifespan for the population. This progress speaks volumes about the positive impact of improved medical treatments and preventative measures.